2002
DOI: 10.1159/000065022
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA Profile in Lipoid Nephrosis: Evidence for Increased IL-8 mRNA Stability

Abstract: Background/Aims: Proteinuria in idiopathic minimal lesion nephrotic syndrome (IMLNS) is presumed to be due to the effect of circulating factors on glomerular permeability to plasma proteins. This study examines the expression of messenger ribonucleic acid (mRNA) for cytokines thought to mediate glomerular inflammation during different stages of the nephrotic syndrome. Methods: Messenger RNA expression and stability from peripheral blood mononuclear cells of IMLNS patients in relapse and in remission, and age m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
7
1
1
Order By: Relevance
“…Elevated IL-2 and IL-10 mRNA levels were documented in patients during relapse, by Shimoyama and colleagues [33]. In our studies, we were unable to detect IL-2 or IL-4 mRNA in the same types of patients [49]. In contrast, Cho et al found elevated spontaneous mRNA expression of IL-4 in IMLNS patients in relapse [28].…”
Section: Cytokine Pattern According To Mrna Expression In Imlns Patiecontrasting
confidence: 80%
See 1 more Smart Citation
“…Elevated IL-2 and IL-10 mRNA levels were documented in patients during relapse, by Shimoyama and colleagues [33]. In our studies, we were unable to detect IL-2 or IL-4 mRNA in the same types of patients [49]. In contrast, Cho et al found elevated spontaneous mRNA expression of IL-4 in IMLNS patients in relapse [28].…”
Section: Cytokine Pattern According To Mrna Expression In Imlns Patiecontrasting
confidence: 80%
“…[36] ↑/N Laflam et al [49] N D ↑/N N/N N/N N/N No biopsy data Bustos et al [37] ↑/N Cho et al [28] ↑ Yap et al [29] N/N N/N N/N ↑/N Shimoyama et al [33] ↑/N N/N N/N ↑/N N/N Intracellular cytokine detection in IMLNS patients in relapse…”
Section: Cytokine Pattern According To Mrna Expression In Imlns Patiementioning
confidence: 99%
“…However, the Northern blot technique does not allow the accurate quantitation of signals and the data might be less reliable than ours. Laflam et al [20] used a ribonuclease protection assay to measure the mRNA expression of IL-4, IL-8, TNF-a, TGFb1, VPGF, IFN-g, Rantes, and MCP-1 in children with INS. They reported that only IL-8 expression was significantly higher in relapse than in remission, but this was not based on paired data.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the serum level of IL-8 and the stability of IL-8 mRNA increase in patients with minimal change disease [8]. It has been reported that patients with polycythemia vera have high serum and bone marrow plasma levels of IL-8 and IL-11 and also increased secretion of these two interleukins from the bone marrow stromal cells [9].…”
Section: Discussionmentioning
confidence: 99%